Cultural preservation as a catalyst for sustainable tourism: Challenges and potentials in Cimande Tourism Village, Indonesia - Soeswoyo, Dina Mayasari; Arafah, Willy; Oktadiana, Hera; Budiman, Surya Fadjar (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: This study aimed to investigate the cultural potential and challenges of preserving the intangible cultural heritage and living culture of Cimande Tourism Village to enhance its development as a sustainable tourism destination. Research Methodology: A qualitative approach was used, with data collected through Focus Group Discussions (FGDs) and in-depth interviews involving cultural practitioners, Kelompok Sadar Wisata (POKDARWIS), local residents, and government officials. Results: The study identified nine key cultural elements, including Pencak Silat , traditional medicine, and local rituals, while highlighting 11 major challenges, including insufficient stakeholder support, low community participation, limited human resource capacity, and minimal use of digital marketing. Conclusions: This study explores the cultural potential and challenges of preserving Cimande Tourism Village, highlighting UNESCO-recognized Pencak Silat. Key strategies include youth engagement, government-community partnerships, improved infrastructure, and digital marketing to strengthen cultural preservation and tourism growth. Limitations: This study focuses on cultural preservation efforts, specifically in Cimande Tourism Village, using qualitative methods such as thematic analysis and CAQDAS NVivo, limiting its scope. Contributions: This study deepens the understanding of how local culture can promote sustainable tourism, particularly in rural areas rich in cultural traditions such as Cimande. These findings provide valuable insights for tourism village managers and local governments to balance cultural preservation with economic growth through tourism. Novelty: This study offers a comprehensive exploration of the integration of local culture with sustainable tourism development in Cimande Village, an area that has not been extensively studied.